4C SKILLS-ORIENTED WORKSHEET IN BIOLOGY FOR STUDENT IN SENIOR HIGH SCHOOL (DEFINING PHASE) - Frichilya Wulan Darry; Rahmadhani Fitri; Oktafianti Oktafianti (Universitas Negeri Padang, 2021)
In the 4.0 revolution era, various skills are needed, one of which is innovation and learning skills known as 4C. The use of learning media in the learning process can help students improve understanding to conclude information and the learning process becomes more interesting when using the right media. Biology learning is also supported by understanding material through learning media, one of which is LKPD because it requires students to understand the material and students will be motivated because at the end of learning students will find understanding of concepts so that learning objectives will be achieved. Based on the questionnaire that has been given to students of class XI Mathematics and Natural Sciences which consists of 6 classes via google form, students are very interested in using LKPD because it makes it easier for students to understand the material that has been given and as many as 96% of students consider that the use of LKPD is very important. in the learning process. The advantage of the LKPD is that it will have a positive impact on the understanding of students and increase the value after using the LKPD.